PERANAN ORANGTUA DALAM MENDUKUNG REGENERASI PETANI PADI (ORYZA SATIVA L) DI DESA SRIKATON KECAMATAN BUAY MADANG TIMUR - Myxa Cezar Ranzez; Oeng Anwarudin; Maspur Makhmudi (Jurnal Inovasi Penelitian, 2020)
One of agent who has a role to play in the regeneration of farmers in one area and can be performed early on is the parent. Parents, therefore, have an important role to play in supporting the regeneration of farmers. Research aims to analyze descriptive and unifying roles that parents play in supporting the regeneration of rice farmers (oryza sativa l) and analyze the effects of the roles of parents of individual characteristics, age, occupational experience, a broader landscape and external factors that include lifestyle, education and government support for the development of rice farmers (oryza sativa l). Research has been conducted in east buay madang, ogan combo east, south Sumatra. The research population is made up of farm parents who make farmers. Samples are selected as many as 70 people using cluser random sampling techniques. The conversion of this study consists of individual characteristics, external factors and the role of parents. Data analysis techniques use desktop statistical analysis mean, percentage and inductive /inferens) that is multiple regression. The results of weavers have been determined to assume that both the external factors and the role of the parents fall into high categories. The role of parents is influenced by external factors. Thus, to preserve the continued role of parents in supporting the regeneration of rice farmers (oryza sativa l) could be done by increasing the external factor of lifestyle, parental role and government support.